A PNDR e o planejamento regional brasileiro no início do século XXI - Simone Affonso da Silva (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– This article aims to present, briefly, the main features of the National Policy for Regional Development (PNDR), as well as its obstacles and the key challenges to its execution and implementation and some proposals contained in its current review process. Established by Decree 6.407, 22th February 2007, the PNDR is characterized simultaneously by resumption, reframing and innovation of political, economic and administrative paradigms present in the national and international scene. These paradigms have significantly influenced the analysis about the brazilian regional problematics and the policies focused on its reduction. However, several limitations in theoretical, political and operational dimensions lead to great difficulties in the implementation and execution of PNDR. Therefore, since 2012, this policy is under review, aiming to overcome part of their obstacles. On this context, it's noteworthy the realization of a national conference and the elaboration of a Bill that will follow the legal channels in the National Congress to establish a new version of this policy.
Keywords: O21; 330; regional planning; National Policy for Regional Development; regional policies